Invasive aspergillosis among heart transplant recipients is rare but causes rapid death due to septic shock and multiple organ dysfunction syndrome - Shields, Ryan K. (2012)
Between 2000 and 2011, proven or probable invasive aspergillosis (IA) was diagnosed in 1.7% (8/455) of heart transplant (HTx) recipients at our center, in the absence of antifungal prophylaxis. All patients had invasive pulmonary infections and 75% (6/8) were diagnosed during 2 separate 3-month periods. Cases were notable for their association with septic shock and multiple organ dysfunction syndrome (MODS) (75%, 6/8 each), non-specific clinical and radiographic findings, and rapid mortality despite mould-active antifungal therapy (88%, 7/8; occuring at a median 11 days after diagnosis). All patients had predisposing conditions known to be risk factors for IA. For patients with early IA (within 90 days of HTx), conditions included hemodialysis, thoracic re-operation, and the presence of another case in the institution within the preceding 3 months. For late-onset IA, conditions included hemodialysis and receipt of augmented immunosuppression. Clinicians should suspect IA in HTx recipients with risk factors who present with non-specific and unexplained respiratory syndromes, including those in septic shock and MODS, and institute prompt antifungal therapy without waiting for the results of cultures or other diagnostic tests.